Women Writers and Old Age in Great Britain, 1750-1850 - Looser, Devoney (Johns Hopkins University Press, 2008)
This groundbreaking study explores the later lives and late-life writings of more than two dozen British women authors active during the long eighteenth century.Drawing on biographical materials, literary texts, and reception histories, Devoney Looser finds that far from fading into moribund old age, female literary greats such as Anna Letitia Barbauld, Frances Burney, Maria Edgeworth, Catharine Macaulay, Hester Lynch Piozzi, and Jane Porter toiled for decades after they achieved acclaim-despite seemingly concerted attempts by literary gatekeepers to marginalize their later contributions.Though these remarkable women wrote and published well into old age, Looser sees in their late careers the necessity of choosing among several different paths. These included receding into the background as authors of "classics," adapting to grandmotherly standards of behavior, attempting to reshape masculinized conceptions of aged wisdom, or trying to create entirely new categories for older women writers. In assessing how these writers affected and were affected by the culture in which they lived, and in examining their varied reactions to the prospect of aging, Looser constructs careful portraits of each of her subjects and explains why many turned toward retrospection in their later works.In illuminating the powerful and often poorly recognized legacy of the British women writers who spurred a marketplace revolution in their earlier years only to find unanticipated barriers to acceptance in later life, Looser opens up new scholarly territory in the burgeoning field of feminist age studies.